COINFECTION BY HEPATITIS B AND HEPATITIS DELTA VIRUSES: MOLECULAR BIOLOGY OF PATHOGENS AND PROSPECTS OF PHARMACOTHERAPY - I. P. Balmasova (Журнал микробиологии, эпидемиологии и иммунобиологии, 2018)
Hepatitis delta virus (HDV) is a defective virus and obligate companion of hepatitis B virus (HBV). The clinical significance of HDV and HBV coinfection is associated with more severe forms of acute or chronic viral hepatitis, a higher risk of developing liver cirrhosis and hepatocellular carcinoma compared to BGV-monoinfection. Current knowledge of the molecular biology of pathogens confirms the existence of a very complex relationship between the HBV, HDV, infected hepatocytes and cells of the immune system. Despite the fact that HBV viremia can now be controlled by using nucleoside analogues in the majority of patients, the problem of treating HDV and HBV coinfection is far from being resolved. Fundamental studies in recent years have led to significant progress in understanding the biology of HDV and provide the basis for the development and introduction into clinical practice highly effective antiviral drugs.